2002
DOI: 10.1124/jpet.102.035022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Renal Cell Repair and Regeneration after Acute Renal Failure

Abstract: In many cases, acute renal failure (ARF) is the result of proximal tubular cell injury and death and can arise in a variety of clinical situations, especially following renal ischemia and drug or toxicant exposure. Although much research has focused on the cellular events leading to ARF, less emphasis has been placed on the mechanisms of renal cell repair and regeneration, although ARF is reversed in over half of those who acquire it. Studies using in vivo and in vitro models have demonstrated the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
121
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 53 publications
2
121
0
1
Order By: Relevance
“…The cell source for regenerating cells is poorly understood, with the strongest evidence supporting a role for less injured tubular cells, which proliferate and migrate to replace the neighboring dead cells, and eventually reline denuded tubules restoring the structural and functional integrity of the kidney [1,2]. Consistently, genetic tagging of renal epithelium in mouse models of acute kidney injury (AKI) indicated that repair of damaged nephrons is predominantly accomplished by intrinsic, surviving cells localized within the nephron epithelium [4].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The cell source for regenerating cells is poorly understood, with the strongest evidence supporting a role for less injured tubular cells, which proliferate and migrate to replace the neighboring dead cells, and eventually reline denuded tubules restoring the structural and functional integrity of the kidney [1,2]. Consistently, genetic tagging of renal epithelium in mouse models of acute kidney injury (AKI) indicated that repair of damaged nephrons is predominantly accomplished by intrinsic, surviving cells localized within the nephron epithelium [4].…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, several studies demonstrated that cells showing a mixed phenotype between parietal and proximal tubular epithelium increase at the tubuloglomerular junction during kidney growth, chronic renal disorders [20][21][22][23], or during ageing [24], suggesting that renal progenitors of Bowman's capsule may be able to change to tubular cells in these conditions. However, during AKI, repair of epithelial cells mostly depends on cells directly derived from the migration and proliferation of adjacent tubular epithelial cells [1,2]. In addition, a recent study in rodents demonstrated that proliferation of regenerating tubular epithelium following acute ischemic injury is stochastically distributed among surviving tubular cells [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTEC require anchorage to the BM for normal function, which is mediated by integrins' binding to ECM proteins, being collagen IV its major component. It was demonstrated previously (38) that ␤1 integrins' binding to collagen IV and not to other ECM proteins elicits signal transduction events in injured PTEC that stimulate cell survival and are important for the recovery of physiologic functions. Our results revealed that ex vivo HUTS-21 was able to increase the adherence of ischemic PTEC to collagen IV, suggesting that in vivo HUTS-21 most probably increases the adhesiveness of ␤1 integrins to the basal lamina, thus contributing to prevent renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration and remodeling of the kidney results in recovery of renal function and morphology by tubular epithelial cell replacement (2,3). However, tubulointerstitial remodeling, as a result of an uncontrolled balance between synthesis and degradation of extracellular matrix (ECM) proteins, also can result in tubulointerstitial fibrosis (4,5), which is an important risk factor for progressive renal function loss (6).…”
mentioning
confidence: 99%